Răspuns :
[tex] \sqrt{(4-\sqrt{17})^2} + \sqrt{(6-\sqrt{17})^2}= ? \\ \\
\to \text{Luam separat} \\ \\
\sqrt{(4-\sqrt{17})^2} = | 4-\sqrt{17}| = \boxed{\sqrt{17}-4} \\ \\
\sqrt{(6-\sqrt{17})^2} = | 6-\sqrt{17}| = \boxed{6-\sqrt{17}} \\ \\ \\ \\
\to \boxed{\sqrt{(4-\sqrt{17})^2} + \sqrt{(6-\sqrt{17})^2}= \sqrt{17}-4 + 6-\sqrt{17} =\boxed{2}} [/tex]
NU este ecuatie
este Ex[presie numerica\de fapt este UN CALCUL
sa ne amintim!
√x²≠x, ci
√x²=|x| adica
√x²=x, daca x≥0
si =-x daca x<0
atunci
√(4-√17)²=|4-√17|
dar
4=√16<√17
atunci 4-√17<0
si
|4-√17|=-(4-√17)=√17-4
si
6=√36>√17
atunci 6-√17>0
deci
|6-√17|=6-√17
deci expresia este
√17-4+6-√17=-4+6+0=6-4=2